2019
DOI: 10.1109/twc.2019.2937763
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Tag Backscattering to MIMO Reader: Channel Estimation and Throughput Fairness

Abstract: Green low power networking with the least requirement of dedicated radio resources is need of the hour which has led to the upsurge of backscatter communication (BSC) technology. However, this inherent potential of BSC is challenged by hardware constraints of the underlying tags. We address this timely concern by investigating the practical efficacy of multiple-input-multiple-output (MIMO) technology in overcoming the fundamental limitations of BSC. Specifically, we first introduce a novel least-squares based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 46 publications
(125 reference statements)
0
22
0
Order By: Relevance
“…A novel least-squares estimator for the forward and backward links between the reader and the tag and also corresponding linear minimum-mean square-error estimate for the backscattered channel are derived in a single-tag BSC setting. The authors further consider multi-tag backscatter setting in [191], as shown in Fig. 9.…”
Section: Multi-antenna and Mimo Systemsmentioning
confidence: 99%
“…A novel least-squares estimator for the forward and backward links between the reader and the tag and also corresponding linear minimum-mean square-error estimate for the backscattered channel are derived in a single-tag BSC setting. The authors further consider multi-tag backscatter setting in [191], as shown in Fig. 9.…”
Section: Multi-antenna and Mimo Systemsmentioning
confidence: 99%
“…For a multiantenna reader, the transmit beamforming (BF) has been optimized taking into account channel estimation using backscatter pilot symbols [12]. Later, sum throughput and throughput fairness have been optimized in space division multiple access (SDMA) by optimizing the transmit BF and receive BF at the reader [18], [19].…”
Section: A Related Workmentioning
confidence: 99%
“…To improve the power-efficiency of IoT devices further, backscatter modulation, sending data by reflecting a carrier signal excited from another source [8], [9], has been addressed into recent IoT applications [10], [11], where IoT devices are exempt from installing powerconsuming active RF circuits and even harvest the energy from the incident carrier. Such backscatter communication (BackCom) networks are classified according to a source emitting a carrier signal: monostatic if the source is also a reader decoding the backscatter signals [12]- [19], bistatic if the source and the reader are different entities [20], and ambient if the source is a transmitter of another network in the vicinity of the reader [21]- [23]. In the networks, backscatter IoT devices (BDs) may reflect the incident carrier signal for backscatter modulation fully or in part or harvest the energy from the carrier signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in this direction propose Multiple Input Multiple Output (MIMO) architectures considering multiple antennas at either node side or illuminator/receiver side. Specifically, traditional space-time coding (STC), beamforming-like techniques, receive and transmit diversity for the forward link, have been adapted for backscattering MIMO systems [ 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%